STRATEGI BERTAHAN HIDUP BURUH TANI SAWIT DI KELURAHAN PASIR SIALANG KECAMATAN BANGKINANG KABUPATEN KAMPAR - Wirdatul Jannah; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in Kelurahan Pasir Sialang Kecamatan Bangkinang Kabupaten Kampar. The purpose of this study was to determine how a survival strategy in the palm farm workers when the economic crisis hit the family household. This study, entitled " survival strategy hodge oil in Kelurahan Pasir Sialang Kecamatan Bangkinang Kabupaten Kampar". Topics focus of this research is how the socio-economic characteristics of the farm workers of oil and how survival strategies palm farm workers in the District Beehive Sand Village Bangkinang Kampar district. The sample of the study was a farm laborer and the farmer oil related institutions such as village officials and workers of PT Johan Santosa. Sampling was done by simple random sampling technique. Samples are numbered 26 people hodge oil and farmer 3. The author uses descriptive quantitative method and the data were analyzed quantitatively. Instruments of data are observation, interview and documentasi. The results showed that the survival strategies implemented respondent is strengthening social relations, following the social gathering activities, borrow money, the utilization of natural resources, diversification of oil workers work family. How to survive the predominant use is to borrow money from neighbors, employers and families, and strengthening social ties with the surrounding community.Keywords: survival strategies, palm farm workers, social and economic.